SELF-HELP CONSOLIDATION CHALLENGES IN LOW-INCOME HOUSING IN SOUTH AFRICA - Judith T. OJO-AROMOKUDU; Claudia LOGGIA (Journal of Construction Project Management and Innovation)
In South Africa, low-income housing is provided by the state by means of subsidies to build a starter house. As a result of accessing housing, it is intended that the socio-economic status of dwellers can improve, allowing them to extend the dwellings to suit the evolving households’ needs. In fact, as shown in many settlements across South Africa, dwellers have attempted to consolidate their dwellings through self-help construction, relying on their limited finances and technical know-how. The inherent know-how of households is expressed in the limited construction methods employed, and where expertise is lacking in the household, assistance is sought from social network groups. This study reports on self-help attempts aimed at consolidating low-income subsidised housing in South Africa. It highlights areas of concern in the consolidation process and argues for a more regulatory framework to create an enabling environment for more sustainable self-help consolidation. A pilot study was conducted in the KwaZulu-Natal Province to assess the informal consolidation challenges, while proposing strategies to enhance the self-help construction practices. Through a qualitative approach based on semi-structured interviews and observations, this study revealed the constraints and impact of informal consolidation attempts on the households’ livelihood and environment. The research focuses on visible efforts made by purposefully selected households. It is hypothesised that if households are given appropriate guidelines to enhance their skills and flexible realistic options through participatory design practices, their housing consolidation efforts will be more resilient and socio-economically sustainable